Electromechanics and MEMS: textbook - Jones T. B. Thomas (Cambridge, Cambridge University Press, 2013)
Offering a consistent, systematic approach to capacitive, piezoelectric and magnetic MEMS, from basic electromechanical transducers to high-level models for sensors and actuators, this comprehensive textbook equips graduate and senior-level undergraduate students with all the resources necessary to design and develop practical, system-level MEMS models. The concise yet thorough treatment of the underlying principles of electromechanical transduction provides a solid theoretical framework for this development, with each new topic related back to the core concepts. Repeated references to the shared commonalities of all MEMS encourage students to develop a systems-based design perspective. Extensive use is made of easy-to-interpret electrical and mechanical analogs, such as electrical circuits, electromechanical two-port models and the cascade paradigm. Each chapter features worked examples and numerous problems, all designed to test and extend students understanding of the key principles.